African public theology - Agang, Sunday Bobai; Hendriks, H. J.; Forster, Dion Angus (Langham Creative Projects, 2020)
Intro -- Foreword -- Preface -- Acknowledgements -- Contributors -- Part 1 Introduction to Public Theology -- 1 The Need for Public Theology In Africa -- 2 The Nature of Public Theology -- 3 The Bible and Public Theology -- 4 The Trinity and Public Theology -- 5 Public Theology and Identity -- Part 2 Public Theology and Public Life -- 6 Democracy, Citizenship and Civil Society -- 7 Work -- 8 Economics -- 9 Poverty -- 10 Rural Community Development -- 11 Education -- 12 The Environment -- 13 Science -- 14 Health -- 15 Human Rights -- 16 Gender -- 17 Migration and Human Trafficking -- 18 Refugees and Stateless People -- 19 Interfaith Relations -- 20 The State -- 21 Police and Armed Forces -- 22 Land Issues -- 23 The Media -- 24 The Arts -- 25 Leadership -- 26 Intergenerational Issues -- Part 3 Public Theology and the Church -- 27 Christianity and the Church in Africa -- 28 Mobilizing the Church in Africa -- 29 Towards the Africa God Wants -- Appendix -- Bibliography.